The possible focal points of small regions's: Harghita County's development in the 2014 - 2020's EU budget period - Eleonóra Barok; Erzsébet Orbán (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
It is a known fact that EU founds absorption rate in Romania is very slow. We were curious about the situation of our region - Center Region - and it's counties, and we wanted to see what are the main differences between the region's counties. We used information from official statistical sites, websites of local authorities, press releases and we also based on own experience. Analyzing the situation, development plans and SWOT results of the counties, we realized that according to infrastructure differences our county in the near future will not be as good performer like Brasov, Sibiu and Mures, so we further focused on similarities. The most important common characteristic of all these counties is the loyalty for land, for culture, for local products. Almost every settlement has something special (pie, sausages, dairy, manufacture products), and the demand for slow- and healthy food is growing. So we have to fructify this like strength, and offer the tourists something special, a piece of our region, our culture, and our rural life. We also have to pay attention of our recognized potato plantations, and exploit the possibilities for livestock-breeding. The main sectors which still need to be developed are the infrastructure, agriculture, tourism and the competitiveness of the companies. All these with the help of educated human resources. So in the next budget period we have to focus to these sectors and pay attention for not only apply for resources just for attracting founds, but to have sustainable projects that will ensure a sustainable development both for individuals, companies and local authorities.
Keywords: 330; EU founds; sustainability; local products; agriculture; tourism